Morphological and molecular characterization of Metaxonchium magnum sp. n. from Iran (Nematoda, Dorylaimida, Belondiridae), with new insights into the phylogeny of the genus. (31st January 2023) - Asgari, M.; Abolafia, J.; Eskandari, A.; Sarafraz-Nikoo, F.; Peña-Santiago, R.
Abstract: A new species of the genus Metaxonchium is described from a natural habitat in Iran. Metaxonchium magnum sp. n. is characterized by its 3.62–4.65 mm long body, lip region cap-like and offset by constriction and 13–16 μm wide, odontostyle fusiform and 14–17 μm long, neck 1016–1359 μm long, both parts of the pharynx separated by a short isthmus-like narrowing, pharyngeal expansion occupying 74.2 (73–77)% of total neck length in females and 70.4 (66–72)% in males, female genital system mono-opistho-ovarian, didelphic, anterior genital branch a large uterine sac with a small terminal mass occupying 7–14% of body length, posterior uterus long and tripartite with a Z-like differentiation, V = 50–52, caudal region short and rounded (24–41 μm, c = 99–161, c′ = 0.5–0.7), spicules 90–105 μm long and 10–13 spaced ventromedian supplements with hiatus. Analysis of D2–D3 28S rDNA sequences of the new species suggests that Metaxonchium might not be a monophyletic taxon, a matter that should be confirmed after future research.